Konsep Humanistik Ditinjau Dari Perspektif Pendidikan Islam - ddin, Fakhru (Insititut Agama Islam Negeri (IAIN) Curup, 2016)
The development of modern education that tends to separate the spiritual and physical education impact to soulless mind and leads to immoral acts which further led to appear new concept of humanization of education as a paradigm of liberation which full western value, thus failing to address the substance of the human humanity. This phenomenon prompted the authors to examine and offer a humanistic concept â?? Islamic Concept against the human values in education. Approach in addressing the core problem of the author refers to the approach to the study of literature. This study found that the paradigm of Islamic education humanist contained in al-Qur`an, and in Islamic education is one activity that aims to please God by taking into account the balance between religious knowledge and general knowledge while providing the freedom to develop science in goal utilization for human life.